A quantitative liability risk assessment of oil spills in oil ports: the case of the Guangdong-Hong Kong-Macao Greater Bay Area. Issue 7 (3rd October 2022) - Zhong, Huiling; Lin, Yishu; Yip, Tsz Leung
ABSTRACT: To mitigate risk and enhance safety in oil ports, this study proposes a method to analyse the civil liability risk and criminal liability risk of oil spills in oil ports. Based on scenario analysis and data analysis, the probability, spill size, number of casualties, actual compensation and total spill cost are estimated for different scenarios, including loading arm/hose rupture and hull failure when a vessel is berthing, manoeuvring near a berth and moving through the port. Based on these estimated factors and legal liability, the civil liability risk and criminal liability risk borne by oil ports and ship owners are estimated. Finally, data from an oil terminal in the Guangdong-Hong Kong-Macao Greater Bay Area are used to verify the applicability of the proposed method. The estimated probability and corresponding consequences can be used to determine which scenario would result in criminal liability and provide a reference for emergency capacity planning. The estimated risks are useful for loss mitigation and crime prevention. The findings and analysis reveal the current low compensation ratio and the inconsistency in criminal standards for oil spills in China. Therefore, the enforcement of civil compensation and unity among criminal standards should be prioritized.